THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON SHIFTING ATTITUDES AND MOTIVATION OF EXTENSION OFFICERS TOWARDS ICT USE IN AGRICULTURAL EXTENSION IN INDONESIA - Chris SUGIHONO; Sunarru Samsi HARIADI; Sri Peni WASTUTININGSIH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The objective of this research is to investigate how transformational leadership influences the shifts in attitudes and motivation of agricultural extension officers (AEOs) regarding the use of Information and Communication Technology (ICT) in agricultural extension. A cross-sectional study was conducted from November 2022 to February 2023 in North Maluku, Indonesia, involving 252 government AEOs as the sample. Data were collected through a survey using a questionnaire that measured transformational leadership, attitudes, and motivation towards ICTs. Linear regression analysis was employed to test the research hypotheses. The results revealed that transformational leadership positively and significantly influenced AEOs’ attitudes (β = 0.309; p < 0.05) and motivation (β = 0.416; p < 0.05) towards ICT utilization. However, transformational leadership alone explained a limited portion of the variance in attitudes (14.4%) and motivation (17.6%), suggesting the influence of other factors. These findings highlight the importance of transformational leadership in fostering ICT adoption among AEOs. However, to maximize the potential of ICT in agricultural extension, a multi-faceted approach is necessary, encompassing not only leadership development but also the provision of adequate resources, infrastructure, training, and supportive institutional norms that encourage ICT utilization.